When and How Should We Respond to Unjust Laws? A Thomistic Analysis of Civil Disobedience - Wyma, Keith David (Christian scholar's review, 2014)
Keith D. Wyma argues that a coherent, well-grounded Christian perspective on civil dis- obedience is possible, and can be found in the work of Thomas Aquinas. Aquinas gives crisp guidelines regarding when civil disobedience could be morally allowable—or even obligatory—and supplies a “test” to determine whether a given method of disobedience is morally appropriate. The article presents a brief summary of Aquinas’ account, notes some ways in which it skillfully navigates scriptural and historical controversies on civil disobedience, and offers a few observations on how Aquinas’ account could be useful to Christians, especially students, today.